Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1099/mic.0.2007/007427-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular type III secretion by cytoplasmic Shigella flexneri promotes caspase-1-dependent macrophage cell death

Abstract: The Gram-negative bacterium Shigella flexneri triggers pro-inflammatory apoptotic cell death in macrophages, which is crucial for the onset of an acute inflammatory diarrhoea termed bacillary dysentery. The Mxi-Spa type III secretion system promotes bacterial uptake and escape into the cytoplasm, where, dependent on the translocator/effector protein IpaB, caspase-1 [interleukin (IL)-1b-converting enzyme] and its substrate IL-1b are activated. Here, we show that in the course of a macrophage infection, IpaB is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 64 publications
(100 reference statements)
3
28
0
Order By: Relevance
“…This hypothesis was supported by a previous study demonstrating that NMI and NMII differentially activated primary human alveolar macrophages, which produced different levels of pro-IL-1␤ and mature IL-1␤ (46). It has been reported that Shigella flexneri induced caspase-1-dependent host cell death, leading to the release of IL-1␤, which causes acute inflammation and ultimately helps clear the infection (47). However, Salmonella-induced apoptosis was correlated to the severity of disease in vivo (48).…”
Section: Discussionsupporting
confidence: 73%
“…This hypothesis was supported by a previous study demonstrating that NMI and NMII differentially activated primary human alveolar macrophages, which produced different levels of pro-IL-1␤ and mature IL-1␤ (46). It has been reported that Shigella flexneri induced caspase-1-dependent host cell death, leading to the release of IL-1␤, which causes acute inflammation and ultimately helps clear the infection (47). However, Salmonella-induced apoptosis was correlated to the severity of disease in vivo (48).…”
Section: Discussionsupporting
confidence: 73%
“…S4 in the supplemental material). Moreover, WR30 efficiently kills macrophages, a process that requires a TTSS that can secrete functional translocators (IpaB and -C) (37,38). The phenotype for WR30 in epithelial cells may be a pleiotropic effect resulting from its filamentous morphology, even though log-phase cultures contain similar numbers of viable bacteria.…”
Section: Vol 78 2010 Characterization Of S Flexneri Msbb Mutants 409mentioning
confidence: 99%
“…The "entry region" of the virulence plasmid contains the mxi, spa, and ipa operons that code for the type III secretion apparatus (T3SA) itself (12). The T3SA resembles a nano-needle and syringe, which consists of a basal body that spans the inner and outer Shigella membranes, a ϳ2.5-nm inner diameter needle that extends from the bacterial surface to provide a passageway for protein translocation and a tip complex that regulates secretion and interacts with the host cell membrane (13,14). The mechanisms supporting protein secretion through the Shigella T3SA remain largely unclear; however, we recently characterized Spa47 as an active T3SS ATPase, suggesting that it may provide the energy necessary to power secretion (15).…”
mentioning
confidence: 99%